Chapter 4 The epistemic status of scientific visualisations - Mößner, Nicola (History and Philosophy of Technoscience, 2018)
As the considerations in the previous chapter made clear, visual representations are, without doubt, part of many epistemic processes in contemporary science. Scientists present diagrams in their publications and talks to communicate their research results. They investigate computer-generated images as substitutes for research objects. Drawings in textbooks are used to educate novices, to introduce them to a new field of knowledge and so on. Moreover, it was pointed out that in quite a few instances images might also be used for non-epistemic purposes, for example to gain the attention of a particular audience